Ischemic heart disease and stroke in male couriers: a cohort study using the national health insurance data and national employment insurance data - Yoon, Jiyoung; Min, Jeehee; Kim, Eun Mi; Kim, Jaiyong; Kim, Inah (Frontiers in Public Health, 2024)
Objectives: This study aimed to determine the risk of ischemic heart disease (IHD) and stroke among male couriers in Korea by linking the National Health Insurance (NHI) and National Employee Insurance (NEI) databases. Methods: As of 2015, the NHI and NEI databases were linked using individual IDs. A cohort of male couriers aged 20–64 years (N=5,012) was constructed using the Korean Employment Insurance Occupational Classification (KECO-2007). A male total wage worker cohort (N=5,429,176) and an office worker cohort (N=632,848) of the same age group were constructed for comparison. Follow-up was conducted until December 31, 2020, to confirm the occurrence of IHD and stroke. The 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) codes was used to define the diagnoses. Using medical services for more than one day of hospitalization or having more than two outpatient visits were also considered. The age-standardized incidence ratio (SIR) was calculated to evaluate the risk of occurrence, and after adjusting for age, alcohol consumption, smoking, obesity, income level, and employment duration as confounding variables, the hazard ratio (HR) was calculated using the Cox model. Results: The SIR of IHD was 1.54 (95% CI 1.31–1.78) for couriers and 1.08 (95% CI 1.06–1.10) for office workers, compared to male total wage workers. Compared to male total wage workers, couriers had a higher SIR of stroke at 1.84 (95% CI 1.40–2.28) while office workers had a lower incidence at 0.86 (0.83–0.89). Compared to total wage workers, couriers had a significantly higher adjusted HR for IHD at 1.60 (95%CI 1.37–1.87) as well as a higher HR for stroke at 1.39 (95%CI 1.07–1.79). Compared to office workers, couriers had a significantly higher HR for IHD at 1.34 (95%CI 1.13–1.59) as well as for stroke at 1.43 (95%CI 1.08–1.88). Conclusions: The incidences of IHD and stroke were higher among male couriers than among male office workers and total wage workers, highlighting the necessity of implementing a public health intervention to prevent IHD and stroke among couriers.